The Influence of Mucus Microstructure and Rheology in Helicobacter pylori Infection - Bansil, Rama; Celli, Jonathan; Hardcastle, Joseph; Turner, Bradley (Frontiers in Immunology, 2013)
The bacterium Helicobacter pylori (H. pylori), has evolved to survive in the highly acidic environment of the stomach and colonize on the epithelial surface of the gastric mucosa. Its pathogenic effects are well known to cause gastritis, peptic ulcers and gastric cancer. In order to infect the stomach and establish colonies on the mucus epithelial surface, the bacterium has to move across the gel-like gastric mucus lining of the stomach under acidic conditions. In this review we address the question of how the bacterium gets past the protective mucus barrier from a biophysical perspective. We begin by reviewing the molecular structure of gastric mucin and discuss the current state of understanding concerning mucin polymerization and low pH induced gelation. We then focus on the viscoelasticity of mucin in view of its relevance to the transport of particles and bacteria across mucus, the key first step in H. pylori infection. The second part of the review focuses on the motility of H. pylori in mucin solutions and gels, and how infection with H. pylori in turn impacts the viscoelastic properties of mucin. We present recent microscopic results tracking the motion of H. pylori in mucin solutions and gels. We then discuss how the biochemical strategy of urea hydrolysis required for survival in the acid is also relevant to the mechanism that enables flagella driven swimming across the mucus gel layer. Other aspects of the influence of H. pylori infection such as, altering gastric mucin expression, its rate of production and its composition, and the influence of mucin on factors controlling H. pylori virulence and proliferation are briefly discussed with references to relevant literature.